Toward an inclusive, healthy, and sustainable Malawi. CIP, CIAT, CIMMYT, ICRAF, ICRISAT, IFPRI, IITA and WorldFish - International Potato Center; International Center for Tropical Agriculture; International Maize and Wheat Improvement Center; World Agroforestry Centre; International Crops Research Institute for the Semi-Arid Tropics; International Food Policy Research Institute; International Institute of Tropical Agriculture; WorldFish (International Potato Center, 2020)
Comprised of 15 top-class research centers, CGIAR is the world’s largest global agricultural innovation network. Eight centers based in Malawi contribute to the national development priorities through an unparalleled combination of skills, knowledge, and partnerships with government, NGOs, academic institutions, and the private sector.